Spillovers, foreign investment, and export behavior - Aitken, Brian; Hanson, Gordon H. 1964-; Harrison, Ann E. (1994)
Case studies of export behavior suggest that firms who penetrate foreign markets reduce entry costs for other potential exporters, either through learning by doing or through establishing buyer- supplier linkages. We pursue the idea that spillovers associated with one firm's export activity reduce the cost of foreign market access for other firms. We identify two potential sources of spillovers: export activity in general and the specific activities of multinational enterprises. We use a simple model of export behavior to derive a logit specification for the probability a firm exports. Using panel data on Mexican manufacturing plants, we find evidence consistent with spillovers from the export activity of multinational enterprises but not with general export activity.
Keywords: Exports; Investments, Foreign